Perempuan sebagai Objek dalam Tren Medusa Trauma di TikTok - Bela, Serly Oktavia Nur; Lubis, Fardiah Oktariani; Ema, Ema; Rahman, Khairul Arief (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The “Medusa Trauma” phenomenon on TikTok represents a new form of female suffering presented as an audio-visual trend. The term is used metaphorically to describe psychological trauma caused by betrayal or abuse by someone close, with the symbol of Medusa from Greek mythology originally a beautiful woman who was cursed into a monster after experiencing sexual violence representing defensive strength born from emotional wounds. This study applies Sara Mills’ model of Critical Discourse Analysis (CDA) to examine the subject and object positions within the Medusa Trauma narrative and how gendered power relations are constructed in digital culture. The analysis is conducted on two levels: micro (textual, audio, and visual representations in TikTok content) and macro (ideological and structural context of patriarchy in digital culture). Previous studies have rarely addressed the representation of women in viral digital trends and the potential commodification of trauma, leaving a research gap that this study aims to fill. The findings reveal that this trend serves not only as a space for emotional expression but also reproduces patriarchal discourse that positions women as passive symbols of suffering. The contribution of this research lies in providing a critical understanding of gender construction in digital culture and its implications for the representation of women’s trauma.